Educational Environment of University - A Model of International Students’ Socio- Psychological Adaptation to the Ethno-Cultural Characteristics of Society - RADEVSKAYA, Nataliya S.; VESELOVA, Elena K.; DVORETSKAYA, Marianna Ya.; KORJOVA, Elena Yu.; MONAKHOVA, Lira Yu. (Journal of Environmental Management and Tourism; Vol 7 No 2 (2016): JEMT Volume VII, Issue 2(14) Summer 2016, 2016)
The relevance of the research problem is caused by the modern discourse of international students’ socio psychological adaptation to the educational environment of high school. Therefore, this article is aimed at the establishment of theoretically and practically based approaches to the development of the model of international students’ socio psychological adaptation to the ethno-cultural characteristics of society in the educational environment of the host university. The paper deals with the socio psychological adaptation typology, structure and content of its species; defines the structure and content of the educational environment as the model of international students’ adaptation to the ethno-cultural characteristics of the society; determines the content of the updating of the educational process of the high school through the realization of ethnocultural training modules focused on the adaptation of international students to the society; substantiates educational - methodical complex. The paper proves the efficiency of the identified educational - methodical complex using students’ readiness criteria: to plan their own interaction with the representatives of ethnic groups in society; to choose cross-cultural alternatives in society; to manage the process of intercultural interaction in society, using a network technology; for perform professional work in the society, and others. The submissions may be useful for social psychologists, teachers, students of psychologists’ and teachers’ improvement and retraining system, methodologists, graduate students and university students.
Keywords: international students; educational environment; socio-psychological adaptation model; ethnocultural features